Chronic ammonia exposure does not influence hepatic gene expression in growing pigs. (27th November 2013) - Cheng, Z.; O'Connor, E. A.; Jia, Q.; Demmers, T. G. M.; Wathes, C. M.; Wathes, D. C.
<x content-type="archive" xml:space="preserve">Abstract</x> Housed pigs are often exposed to elevated concentrations of atmospheric ammonia. This aerial pollutant is widely considered to be an environmental stressor that also predisposes to reduced growth rates and poor health, although evidence to support this view is limited. Hepatic gene expression is very responsive to stress and metabolic effects. Two batches of growing pigs were therefore exposed to a nominal concentration of atmospheric ammonia of either 5 ppm (low) or 20 ppm (high) from 4 weeks of age for 15 weeks. Growth rates were monitored. Samples of liver were taken after slaughter (at ∼19 weeks of age). Samples from the second batch were analysed for global gene expression using 23 K Affymetrix GeneChip porcine genome arrays. Samples from both batches were subsequently tested for five candidate genes using quantitative real-time PCR (qPCR). The array analysis failed to detect any significant changes in hepatic gene expression following chronic exposure to atmospheric ammonia. Animals clustered into two main groups but this was not related to the experimental treatment. There was also no difference in growth rates between groups. The qPCR analyses validated the array results by showing similar fold changes in gene expression to the arrays. They revealed a significant batch effect in expression of lipin 1 (LPIN1), Chemokine (C-X-C motif) ligand 14 (CXCL14), serine dehydratase (SDS) and hepcidin antimicrobial peptide (HAMP). Only CXCL14, a chemotactic cytokine for monocytes, was significantly down-regulated in response to ammonia. As chronic exposure to atmospheric ammonia did not have a clear influence on hepatic gene expression, this finding implies that 20 ppm of atmospheric ammonia did not pose a significant material risk to the health or metabolism of housed pigs.